2019
DOI: 10.1007/s11769-019-1037-8
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Correlation Between Landscape Characteristics and Total Nitrogen in Wetlands Receiving Agricultural Drainages?

Abstract: In the case of increasing fragmentation of wetlands, the study of the relationship between wetland landscape characteristics and total nitrogen (TN) in water is of great significance to reveal the mechanism of wetland water purification. Taking the Naoli River (NR) wetlands in Northeast China as the research object, 10 uniformly distributed sampling sites in the study area were sampled in August 2015 to test the TN concentration and interpret the images of NR wetlands in the same period. Taking the sampling si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In 2015, 450 kg/hm 2 corresponded to paddy fields, and 325 kg/hm 2 corresponded to dry farmland. The concentrations of nitrogen in wetland water have been increasing, primarily due to the discharge of agricultural drainage into the fragmented wetlands [28]. A total of 8 main plant types were recorded in the wetlands, including weeds (WS), Nymphoides peltata-Nymphoides cristatum (N-N), Deyeuxia angustifolia (DA), Typha orientalis (TO), Carex heterolepis (CH), Phragmites australis (PA), Carex appendiculata (CA), and Zizania latifolia (ZL) [29].…”
Section: Study Areamentioning
confidence: 99%
“…In 2015, 450 kg/hm 2 corresponded to paddy fields, and 325 kg/hm 2 corresponded to dry farmland. The concentrations of nitrogen in wetland water have been increasing, primarily due to the discharge of agricultural drainage into the fragmented wetlands [28]. A total of 8 main plant types were recorded in the wetlands, including weeds (WS), Nymphoides peltata-Nymphoides cristatum (N-N), Deyeuxia angustifolia (DA), Typha orientalis (TO), Carex heterolepis (CH), Phragmites australis (PA), Carex appendiculata (CA), and Zizania latifolia (ZL) [29].…”
Section: Study Areamentioning
confidence: 99%
“…At the same time, due to a lack of oxygen in the wetland filtration bed, the removal of ammonia is limited [32]. Significant nitrate reduction is commonly observed in stormwater wetlands, but total nitrogen reduction depends on the species and concentration of incoming nitrogen [32,33]. Several studies have demonstrated that wetland can effectively remove the total nitrogen (TN) with a median removal efficiency of 37%, and that this reduction significantly correlates with the hydrological loading rate and temperature [31].…”
Section: Introductionmentioning
confidence: 99%